The impact of accommodation taxes on outbound travel demand from the United Kingdom to European destinations - Heffer-Flaata, Hedvig; Voltes-Dorta, Augusto; Suau-Sanchez, Pere (SAGE, 2020)
Despite the progressive introduction of accommodation taxes in many European cities, there is no consensus in the literature as to whether they have positive or negative effects. This may be related to the lack of estimates of the elasticity of visitor demand to accommodation taxes. To fill this gap, we carry out two panel-data regressions using a data set of airline travelers from UK cities to Spanish, French, and Italian destinations between 2012 and 2018. The results from the two-stage least squares regressions indicate that UK international travelers are indeed sensitive to hotel taxes. However, the impact of these taxes differs between peak and off-peak periods and across destination countries, with French destinations showing the most negative effect on visitor flows. The analysis of tax elasticities at a destination level also reveals the lack of a significant negative impact on visitor flows to major cities like Venice or Barcelona.
Keywords: tourist taxes; accommodation taxes; international travel; demand elasticities; panel-data regression